2007
DOI: 10.1196/annals.1406.040
|View full text |Cite
|
Sign up to set email alerts
|

The Population Biology of Coccidioides

Abstract: Studies of field- and patient-derived isolates conducted over the past 75 years have provided a general picture of the population structure of Coccidioides, the cause of coccidioidomycosis. Premolecular studies provided a general outline of the geographical range, epidemiology and distribution of the fungus. Recent studies based on molecular markers have demonstrated that the genus is comprised of two genetically diverse, and genetically isolated, species: Coccidioides immitis and C. posadasii. Both species ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…In addition, we have identified all orthologs of the mating machinery in both C. immitis and C. posadasii (see Table S4 in the supplemental material), although no evidence of sexual structures has yet been uncovered. It is well known that the Coccidioides genus represents a cryptic speciation (65), and there is also evidence of a recombination process in this genus (66), supporting the existence of a sexual cycle. Furthermore, the ratio of MAT1-1/MAT1-2 idiomorphs is 1:1, providing molecular support for the presence of a sexual stage in the life cycle (40).…”
Section: Figmentioning
confidence: 91%
“…In addition, we have identified all orthologs of the mating machinery in both C. immitis and C. posadasii (see Table S4 in the supplemental material), although no evidence of sexual structures has yet been uncovered. It is well known that the Coccidioides genus represents a cryptic speciation (65), and there is also evidence of a recombination process in this genus (66), supporting the existence of a sexual cycle. Furthermore, the ratio of MAT1-1/MAT1-2 idiomorphs is 1:1, providing molecular support for the presence of a sexual stage in the life cycle (40).…”
Section: Figmentioning
confidence: 91%
“…P. brasiliensis, the causative agent of paracoccidioidomycosis, is widespread in Latin America (262). C. immitis and C. posadasii are causative agents of coccidioidomycosis, or valley fever, which is endemic to the Southwestern United States and Central and South America (13). B. dermatitidis is the causative agent of blastomycosis and is endemic to the Americas (26).…”
Section: Sex In Dimorphic Fungi and Dermatophytesmentioning
confidence: 99%
“…Because coccidioidomycosis is increasing and disease severity is highly variable, defining genotypic distribution is important for monitoring outbreaks and determining whether increased pathogenicity is an emerging trait ( 24 ). Previous analysis showed that a single clone did not cause the rise in infection rates in Arizona; rather, each isolate recovered from a patient was unique ( 25 ).…”
mentioning
confidence: 99%